Effect of alpha-1antitrypsin,adiponectine,leptein in obesity - Mahmood, Halla G. (Journal of the Faculty of Medicine Baghdad, 2014)
Background:- Obesity is associated to significant disturbances in endocrine function. Hyper insulinemia and insulin resistance are the best known changes in obesity, but their mechanisms and clinical significance are not clearly established.Objectives:- to investigate the relationship between alph-1 antitrypsin,leptein,adiponectein in  serum of an obese population to find new markers for treating obesity and related disease.Patients and methods:-This study had included thirty patients with obese (12 male and 18 female) with age ranged between 30-45 years and thirty apparently subjects matched for age and weight have been studied, attending the out patients consultation clinic of Baghdad teaching hospital in medical city. The levels of A1AT, adiponectin, leptin, within the centrifuged samples were tested using the ELISA kits purchased from the Millipore CorporationResults:- Result obtained in the present study showed that serum levels of alph-1antitrypsin  and  adiponectin were significantly lower in obese patients than in healthy control.while the serum level of leptin was significantly higher in obese patients than in healthy control.Conclusion:-levels of alpha-1antitrypsin in human serumcorrelate strongly with BMI and also with serum levels of adiponectin, and leptin. These results suggest that alpha-1antitrypsin might be useful as a biomarker and be a potential target for treating obesity.